Individualizatsiya trenirovochnykh nagruzok sportsmenok, zanimayushchikhsya begom na 400m i na 400m s bar'erami - Gzhivoch, R. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
The purpose of this study was to form the complex of objective indices characterizing the physical preparadness of female athletes specializing in 400 m race and 400 m hurdle race and to define the individual training loads for each sportswoman. 24 sportswomen of various qualification acted as subjects of this research. The model characteristics of the sportswomen's physical preparadness and training loads for their training were elaborated. The offered criteria of the physical preparadness'es evaluation in sportswomen became usful for elaboration of their individual training loads.